2000
DOI: 10.1093/jigpal/8.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-based methods for modal logics

Abstract: In this paper we give an overview of resolution methods for extended propositional modal logics. We adopt the standard translation approach and consider different resolution refinements which provide decision procedures for the resulting clause sets. Our procedures are based on ordered resolution and selection-based resolution. The logics that we cover are multi-modal logics defined over relations closed under intersection, union, converse and possibly complementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 24 publications
4
62
0
Order By: Relevance
“…The translation is similar to the one used in [46,48]; other structural translations have been used in [10,25,26,28], for instance.…”
Section: Theorem 3 Let L Be a Dynamic Modal Logic With Any Subset Of mentioning
confidence: 99%
See 3 more Smart Citations
“…The translation is similar to the one used in [46,48]; other structural translations have been used in [10,25,26,28], for instance.…”
Section: Theorem 3 Let L Be a Dynamic Modal Logic With Any Subset Of mentioning
confidence: 99%
“…In this paper we discuss and extend an approach of developing tableaux calculi for modal logics that has been suggested and followed in our previous work [10,19,25,26,28,46,48]. Although resolution calculi apparently operate considerably differently from tableau calculi, we have shown that it is possible to linearly simulate many forms of modal logic or description logic tableau calculi with standard techniques of first-order resolution theorem proving.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The key to achieving this is to extend the clause set in Table 2 to cover the new constructors, and to prove that Lemma 2 still holds. We believe we can do this along the lines of [17,16]; the main technical difficulty is to precisely describe the interaction between the new types of clause and clauses of type Q1. Once this is done, however, the rest of this paper (i.e., the material in the following two sections), should hold with only minor changes.…”
Section: ⊓ ⊔mentioning
confidence: 99%